Cultural influences on B2B service quality-satisfaction-loyalty 客户的文化背景如何影响其对B2B (企业对企业) 服务素质的满意度和忠诚度 - Lee, Myungho; Kang, Mincheol; Kang, Juyoung (Service Industries Journal, 2019)
The link between service quality, customer satisfaction, and customer loyalty has drawn the attention of both academic researchers and practitioners. They are also focusing on the effect of cultural differences on customer attitudes and behaviour in the global service industry. This paper examines the relationships between service quality, customer satisfaction, and loyalty as well as the moderating effect of cultural differences on the above relationships in the industrial business-to-business (B2B) service sector. The paper presents an empirical study using datasets collected from 7652 industrial customers across 55 countries and uses structural equation modeling (SEM) to test the hypotheses. The application of Net Promoter Score (NPS) as a customer loyalty metric based on customer experience management (CEM) is studied in relation to customer satisfaction. The study results demonstrate the positive relationship of service quality, satisfaction, and loyalty. In terms of the effect of cultural differences, the study finds that cultural dimensions of uncertainty avoidance negatively moderate the relationship between service quality and satisfaction, while individualism positively moderates the relationship between service quality and satisfaction. However, cultural differences do not impact on the relationship between satisfaction and loyalty.
Keywords: cultural difference; customer loyalty; customer satisfaction; NPS; Service quality